Media Pembelajaran Pengenalan Bahasa Arab Studi Kasus Madrasah Ibtidaiyah Berbasis Android: Learning Media Introduction to Arabic Case Study of Madrasah Ibtidaiyah Based on Android - Ghea Paulina Suri; ‪Atman Lucky Fernandes; Syahrul Bahri (Engineering and Technology International Journal, 2021)
This study discusses Arabic learning media, which is a tool to convey material used to assist teachers or teachers in delivering a lesson, as well as an alternative to facilitate students, especially students of Madrasah Ibtidaiyah in learning Arabic. The making of Arabic learning media uses Adobe Flash CS6 Professional, while in the design it uses Storyboards, Navigation Structures, and Flowcharts. The test results on this learning media as a whole are 33% stating Very Good, 29% stating Good, and 8% stating Less Good. This shows that more than 60% of respondents stated that this learning media has been running well. While the test on the display of learning media that can attract interest in learning is as much as 60% stating Very Good, 30% stating Good, and 10% stating Less Good. This can indicate that 90% of this learning media can attract learning interest.